Assessment of Knowledge, Attitude and Practice of Pharmacovigilance among Healthcare Professionals: A Cross-sectional Study at a Tertiary Hospital in Eastern Nepal - Chaudhary, Aswani; Sarraf, Deependra Prasad (Birat Journal of Health Sciences, 2024)
Introduction: Adverse drug reactions (ADRs) pose a major concern worldwide causing substantial morbidity and mortality. Healthcare professionals involved in identification, documentation and reporting of ADRs are the pillars of a pharmacovigilance program. Lack of knowledge influence the ADR reporting by healthcare professionals. Objective: To assess knowledge, attitude and practice of pharmacovigilance among healthcare professionals working at Koshi Hospital, Biratnagar, Nepal. Methodology: A descriptive cross-sectional study was conducted among healthcare professionals working at Koshi Hospital, Biratnagar, Nepal from August-December 2021 using a semi-structured proforma. Ethical clearance was obtained from Nepal Health Research Council, Kathmandu (396/2021P). The data were entered into Microsoft Excel 2010 and the descriptive statistics like mean, standard deviation, frequency and percentage were calculated. Statistical Package for the Social Sciences (version 11.5) was used for all statistical analysis. The findings were presented as tables and graphs. Results: Out of 88 healthcare professionals, 57 (64.77%) were females and 35 (39.77%) were staff nurse. Fifty-six (63.64%) participants knew that Department of Drug Administration is the authorized National center for pharmacovigilance program in Nepal. Thirty-six (40.91%) participants had good knowledge and 52 (59.09%) had poor knowledge of pharmacovigilance. Seventy-nine (89.77%) participants had positive attitude and 41 (46.59%) participants had poor practice. Seventy (79.55%) participants had not seen ADR reporting form. Conclusion: The healthcare professionals had insufficient knowledge, positive attitude and poor practice of pharmacovigilance. Efforts are required to enhance knowledge and good practice among healthcare professionals toward pharmacovigilance and ADR reporting which would ultimately strengthen the pharmacovigilance program.